Effects of Brazilian green propolis extract on planktonic cells and biofilms of multidrug-resistant strains of Klebsiella pneumoniae and Pseudomonas aeruginosa - Santos, Pâmela Beatriz do Rosário Estevam dos [UNESP]; Ávila, Damara da Silva [UNESP]; Ramos, Lucas de Paula [UNESP]; Yu, Amanda Romagnoli [UNESP]; Santos, Carlos Eduardo da Rocha [UNESP]; Berretta, Andresa Aparecida; Camargo, Samira Esteves Afonso; Oliveira, Jonatas Rafael de; Oliveira, Luciane Dias de [UNESP] (Taylor & Francis, 2020)
Propolis could represent an alternative therapeutic agent for targeting multidrug-resistant bacteria due to its antimicrobial potential. The effect of Brazilian green propolis (BGP) aqueous extract (AqExt) was evaluated on eight multidrug-resistant clinical strains of Klebsiella pneumoniae and Pseudomonas aeruginosa, as well as on one reference strain for each bacterial species. The minimum bactericidal concentration (MBC) was determined and optimal concentrations were further evaluated in comparison with 0.12% chlorhexidine. The natural extract was chemically characterized by HPLC-DAD analysis. The MBC values ranged between 3.12 and 27.5 mg ml−1. Analysis of bacterial metabolic activity after treatment for 5 min with BGP-AqExt revealed a strong antimicrobial potential, similar to chlorhexidine. The extract comprised several active compounds including quercetin, gallic acid, caffeic and p-coumaric acid, drupani, galangin, and artepillin C. Altogether, the findings suggest that BGP-AqExt is fast and effective against multidrug-resistant strains of K. pneumoniae and P. aeruginosa in planktonic cultures and biofilms.
Keywords: Biofilm; Brazilian green propolis; Klebsiella pneumoniae; multidrug-resistant bacteria; Pseudomonas aeruginosa